Discursive construction of national unity in Nigerian newspaper congratulatory announcements - Jibril, Tanimu Ahmed (2018)
In postcolonial Nigeria, the realisation of genuine national unity within its ethnically diverse society has always been the primary challenge facing the country ever. The situation of the fragmented state of the country is ripe for the national unity discourse to take root, and consequently, a fertile soil for various parties to participate in the grand discourse in different ways. Utilising CDA and, specifically, Fairclough’s (1989, 1992, 1993, 1995a, 1995b) proposed three steps of analysing discourse, the agenda-setting theory (McCombs & Shaw, 1972), present study examined the discursive construction of unity through privately sponsored newspaper congratulatory announcements (NCAs) published in The Guardian, the Vanguard, the Daily Trust and the Punch newspapers. The study was focused on how unity discourse is manipulated to get other discursive actions performed in tandem with the promotion of unity by the private individuals/organisations sponsoring the NCAs. The study also highlighted the way semiotic resources were used to construct the representations of unity as well as how specific discursive strategies were employed to reproduce, normalise and promote such representations. The selected NCAs analysed in the present study covered the period between 2011 and 2016. The textual components of the NCAs were investigated to: (i) to identify the recurrent themes dominating the NCAs discourse; (ii) to describe the semiotic resources and the discursive strategies used to construct, normalise and promote unity in the NCAs; (iii) to examine the type of national unity and version of reality presented by the private sponsors of the NCAs and, (iv) to discuss further discursive actions performed in the name of promoting unity in the NCAs and how it serves the interests of its sponsors. The results from the NCAs discourse analysis revealed five key themes, which were centred on the following: (i) forging unity through peaceful coexistence; (ii) forging unity through patriotic values; (iii) forging unity through diversity; (iv) forging unity through nation building; and (v) forging unity through cultural diversity. Discursive strategies such as abstraction, evaluation, substitution, foregrounded or backgrounded elements, presences and absences were used to manipulate the social reality and the status quo (Carvalho, 2008) so as to discursively recontextualise, normalise and promote (Machin, 2013; van Leeuwen, 2013) the ideology of unity as envisioned by the sponsors of the NCAs. The study discovered that the discursive construction of unity was also linguistically realised through the processes of lexicalisation and metaphorisation. The dominant themes, the semiotic structures and the discursive strategies appeared to have been used to positively manipulate the social reality so as to reproduce, naturalise and promote the concept of unity (see Carvalho, 2008). The study found that the current state and the envisioned future of the country is positively constructed and projected as a united reality by the sponsors of the NCAs, which is contrary to the common perception and lived experiences of the people. Further, the study found that other discursive actions were realised, in the name of promoting unity, by the sponsors of the NCAs. These actions include: pseudopatriotism, commercialisation and corporate social responsibility. The study suggested that these corporate entities and, most especially, the global corporations among them, utilise pseudo acts to boost profits, enhance customer index and work out on their corporate image in the eyes of the ruling regimes as well as the general public within their host communities. The findings of this study are hope to lighten up our understanding of how individuals or corporate organisations may interfere with media coverage (Fairclough, 1995b) and attempt to control and manipulate discourses (Abousnnouga & Machin, 2008; Carvalho, 2008) so as to achieve further ideological or commercial objectives (Hall, 2006). It is also hoped that this study will modestly contribute to the field of critical discourse analysis and other disciplines such as media and communication studies, journalism, visual communication and the literature of media research in general.